Effect of hurdling step strategy on the kinematics of the hurdle clearance technique - Rowley, L. J.; Churchill, S. M., Dunn, M.; Wheat, J. (Sports Biomechanics, 2024)
Athletes use either an eight-step or a seven-step strategy to reach the first hurdle in the 110 m hurdles event. This study investigates the effect of step strategy on the hurdle clearance technique and spatio-temporal parameters of the four steps prior to hurdle clearance. Two-dimensional video data were collected in the sagittal plane from 12 male sprinters, grouped as seven-step (n = 6) or eight-step (n = 6) strategists. The take-off distance was 0.20 m further from the hurdle and the touchdown was 0.42 m closer to the hurdle for seven-step athletes. Additionally, seven-step athletes reduced the length of the final step before hurdle take-off by 0.14 m compared with the previous step, whereas the eight-step athletes extended their final step by 0.17 m. There was negligible difference between the mean horizontal velocities of the two groups throughout the hurdle clearance (0.02 m/s) or the approach time to the first hurdle from the block clearance (0.01 s). This presents an important first insight into the effect of the step strategy on the first hurdle kinematics. Our findings identify the take-off and touchdown distance parameters of the hurdle clearance technique, and approach step characteristics for a successful seven- or eight-step approach strategy to be employed.